What caused the post-pandemic era inflation in Belgium? Replication of the Bernanke-Blanchard model for Belgium - Gregory De Walque; Thomas Lejeune (National Bank of Belgium, 2024)
This paper reports the estimation and simulation of the Bernanke and Blanchard (2023) model on Belgian data. The model offers a consistent framework that ties together wage growth, inflation expectations and price inflation. It is used to study the surge and persistence of inflation in the post-pandemic period in Belgium. According to the model, a sequence of shocks to product shortage, energy and food components is found to be the main reason behind the duration of high Belgian inflation in this period. Though the Belgian replication of the model predicts sensitive short-term inflation expectations to realised inflation, a large wage catch-up - reflecting automatic wage indexation - and some role for labour market tightness in wage growth, their contribution to a persistent inflation is strongly attenuated by a weak estimated wage-price pass-through.
Keywords: E31; E24; E37; 330; inflation; wage indexation; inflation expectations; shortages; energy prices; food prices